2012
DOI: 10.1080/09297049.2011.625355
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and nonnumerical estimation in children with and without mathematical learning disabilities

Abstract: There are currently multiple explanations for mathematical learning disabilities (MLD). The present study focused on those assuming that MLD are due to a basic numerical deficit affecting the ability to represent and to manipulate number magnitude ( Butterworth, 1999 , 2005 ; A. J. Wilson & Dehaene, 2007 ) and/or to access that number magnitude representation from numerical symbols ( Rousselle & Noël, 2007 ). The present study provides an original contribution to this issue by testing MLD children (carefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
53
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 53 publications
8
53
0
6
Order By: Relevance
“…With respect to number production, our results also confirmed those of studies showing that children with MLD were impaired in tasks consisting of transcoding numerosities in spoken numbers (for example, Olkun et al, 2015;Mazzocco et al, 2011;and Mejias et al, 2012). In the present study, we found that children with MLD were less precise than TD children when asked to produce numbers in both analogic-to-symbolic and symbolicto-analogic number transcoding tasks.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…With respect to number production, our results also confirmed those of studies showing that children with MLD were impaired in tasks consisting of transcoding numerosities in spoken numbers (for example, Olkun et al, 2015;Mazzocco et al, 2011;and Mejias et al, 2012). In the present study, we found that children with MLD were less precise than TD children when asked to produce numbers in both analogic-to-symbolic and symbolicto-analogic number transcoding tasks.…”
Section: Discussionsupporting
confidence: 81%
“…Some of this uncertainty stems from significant differences in the methods and tasks used to measure numerical skills in children. In previous studies, researchers usually used comparison tasks to assess numerical abilities in children with MLD and mainly found that they presented deficits in processing Arabic numbers (Davidse et al, 2014;De Smedt & Gilmore, 2011;Desoete et al, 2012;Ferreira et al, 2012;Landerl & Kölle, 2009;Mejias et al, 2012;Mussolin et al, 2010;Piazza et al, 2010;Price, Holloway, Räsänen, Vesterinen, & Ansari, 2007;Rousselle & Noël, 2007). Spoken numerals are nonetheless as important as Arabic numerals in school as well as in daily life activities and should also be considered in studies designed to address the functional origin of MLD.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported a significant correlation between CV and mathematical skills in children (e.g., Mejias, Mussolin, Rousselle, Grégoire, & Noël, 2012;Mejias and Schiltz, 2013) whereas others (Castronovo & Göbel, 2012, experiments 3 & 4) observed that the veridicity of the estimates correlated with math ability in adults, but found no relationship between individual CVs and math ability. Thus, similarly to the findings based on the Weber fraction, it is still unclear ASSESSING THE APPROXIMATE NUMBER SYSTEM whether there is a relationship between CV and arithmetic skill.…”
mentioning
confidence: 98%